HERITABILITY OF AEROBIC POWER OF INDIVIDUALS IN NORTHEAST BRAZIL - Alonso, L; Souza, EC; Oliveira, MV; do Nascimento, LFE; Dantas, PMS (Biology of Sport, 2014)
The objective of this study was to evaluate the genetic and environmental contribution to variation in aerobic power in monozygotic (MZ) and dizygotic (DZ) twins. The sample consisted of 20 MZ individuals (12 females and 8 males) and 16 DZ individuals (12 females and 4 males), aged from 8 to 26 years, residents in Natal, Rio Grande do Norte. The twins were assessed by a multistage fitness test. The rate of heritability found for aerobic power was 77%. Based on the results, the estimated heritability was largely responsible for the differences in aerobic power. This implies that such measures are under strong genetic influence.